A comprehensive view of regional economic development in Finland - Jussi Ahokas (European Regional Science Association (ERSA), 2010)
Regional economic development has become a widely popular research subject within economics and economic geography. The rise of the 'new economic geography' in economics and the recent development in economic geography with (among others) institutional, evolutionary and relational 'turns' have introduced a considerable number of new conceptual and theoretical instruments that can be utilised in the analysis of regional development. The variety of different approaches has certainly produced many positive outcomes for the discipline and the picture of regional economic development has emerged. Yet, at the same time the field of regional economic development studies has become somewhat fragmented. While researchers are working with some special theoretical frameworks and while they are concentrating on some specific issues, the general view of the regional economic development remains fuzzy. Therefore, the aim of this paper is to illustrate prospects for examining regional economic development in a broader scope. The theoretical basis for the study is derived from institutional economic geography and political economy. It is argued that regional economic development process should be understood as a multi-level dynamic spatial process where different institutional, economic and political development paths interconnect and interact. The enquiring of these paths and their underlying mechanisms in detail deepens and diversifies the understanding of regional economic development process. The empirical part of the study concentrates on the different paths and institutional settings that have contributed to the regional economic development within the national borders of Finland. Although the research subject is a nation state, open system methodology is employed and relational aspects of regional economic development are recognised. By exposing the driving mechanisms of regional development process and by investigating their implications at different spatial scales a comprehensive view of regional economic development in Finland is obtained.
Keywords: 330